Implementasi Sistem Manajemen Bimbingan dan Konseling Online dengan Metode FAST (Framework For the Applications of System Thinking) - Romi Andrianto; Muhamad Arief Yulianto (Journal of Research and Publication Innovation, 2024)
A good student monitoring process can be created by having intense communication between the homeroom teacher and the BK for every student's inappropriate actions that require special handling. In their activities, each homeroom teacher has a special agenda book that contains the student's overall identity and a record of their history during their time as a student for any violations they have committed. However, it is not uncommon for the agenda book to be lost, damaged, and at any time requires data updates which of course will be troublesome if it is still done in writing, especially since the agenda book will continue to be transferred to the homeroom teacher in the following year. Homeroom teachers and BK also often lose documents such as student agreement letters and other documents related to students, even if they are stored, it will be quite difficult to find them because of the large number of students. Based on the background that has been described, the author builds and applies a system that can provide convenience for homeroom teachers and BK in the process of recording the identity and history of student actions which can be traced easily and quickly at any time so that the process of providing special guidance can be carried out immediately. The method in building the system uses the FAST method (Framework for the Applications of System Thinking) and uses the ISO/IEC 25010 instrument in the application evaluation. Based on the results obtained from the functional suitability instrument, the system is said to be good because the results are close to 1. The application is also said to be feasible because it can load pages under 7 seconds based on the work efficiency instrument. Based on the analysis of usability, the system has a feasible criterion with a value of 93.8%, from the aspect of system reliability it meets the aspect with a value of ≥95%, and has a grade A in the portability instrument.